Model reference adaptive control based mopid controller for independent steer-by-wire system - Hamdi, Muhammad Haziq (2025)
Recent developments in Steer-by-Wire (SBW) systems have enabled new opportunities for steering without mechanical linkages. However, most existing studies either apply advanced control strategies to simplified vehicle models or employ basic controllers with high-fidelity models, which limits the accuracy of performance evaluation. This study addresses that gap by integrating a Model Reference Adaptive Control (MRAC) strategy with a comprehensive fourteen-degree-of-freedom full-vehicle model, enabling a realistic and robust assessment of an Independent Steer-by-Wire (ISBW) system. The proposed controller is implemented and tested in MATLAB Simulink and validated against CarSim as a benchmark. Simulation results from a double lane change test at 110 km/h indicate that MRAC reduces yaw rate error to 3.33, compared with 11.67 using a conventional PID and 16.67 using a multi-order PID. This represents performance improvements of more than seventy percent. MRAC also maintains lateral acceleration and sideslip angle errors within five percent, outperforming conventional controllers in both accuracy and stability. These findings demonstrate that combining a high-order vehicle model with an adaptive control approach significantly enhances steering performance, offering useful insights for the development of safer and more responsive steering systems.